Les formations eruptives hercyniennes de la cordillere orientale de colombie (1962)
The magmatisme of the Oriental Cordillera of Colombia has been put on evidence. This magmatisme is characterized by association of granites, microgranites and rhyolites. These igneous rocks are evidently the result of a reactivation of the ancient basement and are post or a-tectonic.